Magyk - Sage, Angie; Zug, Mark (New York : Katherine Tegen Books, 2005)
After learning that she is the Princess, Jenna is whisked from her home and carried toward safety by the Extraordinary Wizard, those she always believed were her father and brother, and a young guard known only as Boy 412--pursued by agents of those who killed her mother ten years earlier.
Library binding copy does not come with CD.
Keywords: Princesses -- Fiction; Wizards -- Fiction; Magic -- Fiction; Fantasy